2006
DOI: 10.1002/sca.4950280301
|View full text |Cite
|
Sign up to set email alerts
|

Nanotip electron gun for the scanning electron microscope

Abstract: Experimental nanotips have shown significant improvement in the resolution performance of a cold field emission scanning electron microscope (SEM). Nanotip electron sources are very sharp electron emitter tips used as a replacement for the conventional tungsten field emission (FE) electron sources. Nanotips offer higher brightness and smaller electron source size. An electron microscope equipped with a nanotip electron gun can provide images with higher spatial resolution and with better signal-to-noise ratio.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…It is noted that for other emitter types the effect of Coulomb interactions may actually be dominant, yielding a practical brightness largely determined by the interactions occurring between the emission site and the extractor. We expect this to be the case for the new source types based on carbon nanotubes [Jon04] and nanotips [Vla06].…”
Section: Adding Contributions Togethermentioning
confidence: 90%
See 1 more Smart Citation
“…It is noted that for other emitter types the effect of Coulomb interactions may actually be dominant, yielding a practical brightness largely determined by the interactions occurring between the emission site and the extractor. We expect this to be the case for the new source types based on carbon nanotubes [Jon04] and nanotips [Vla06].…”
Section: Adding Contributions Togethermentioning
confidence: 90%
“…have a Gaussian source intensity profile with a temperature dependent width. [Haw96b] For other source types only their shape is known, such as for liquid metal ion sources (which have a shape with much stronger tails than the Gaussian [War88]) or both shape and size are unknown, such as for the nanotube [Jon04] or the nanotip [Vla06] emitter. In that case the practical brightness of the source can only be found by measuring the source intensity profile.…”
Section: How To Get the Practical Brightness Of A Sourcementioning
confidence: 99%
“…Unfortunately, it is so that the higher this "intrinsic" practical brightness, the more important the effect of Coulomb interactions becomes. For Schottky emitters, it has been shown that interactions become important when the intrinsic practical brightness exceeds ϳ3 ϫ 10 8 A / m 2 sr V. 12 For the new source types based on carbon nanotubes 13 and nanotips, 14 we expect their practical brightness to be largely determined by the Coulomb interactions.…”
Section: Coulomb Interactions Close To the Emittermentioning
confidence: 99%
“…For some source types, this is known and does not need to be measured: thermionic emitters, e.g., have a Gaussian source intensity profile with a temperature dependent width. 16 For other source types, only their shape is known, such as for liquid metal ion sources, which have a shape with much stronger tails than the Gaussian, 17 or both shape and size are unknown, such as for the nanotube 13 or the nanotip 14 emitter. In that case, the practical brightness of the source can only be found by measuring the source intensity profile.…”
Section: How To Get the Practical Brightness Of A Sourcementioning
confidence: 99%
“…The significant improvement was important for high current density, high resolution, high brightness, and low energy spread [ 1 , 2 , 3 ]. Considerable attention was paid to the development of the electron source for electron beam microscopy [ 4 , 5 , 6 , 7 , 8 , 9 ]. In recent years, carbon nanotubes (CNTs) have been considered field emission (FE) materials because they have remarkable properties such as high aspect ratio [ 10 ], high electrical conductivity [ 9 , 11 ], high thermal conductivity [ 12 , 13 ], and high mechanical strength [ 14 ], which make them extremely attractive as nanoscale reinforcements in high-performance composites.…”
Section: Introductionmentioning
confidence: 99%